Detailed Analysis and Radiomic Prediction of First Progression Sites of First-Line Targeted Therapy for EGFR-Mutant Lung Adenocarcinoma Patients With Systemic Metastasis - Li, Xiaoyang; Hou, Runping; Yu, Wen; Zhu, Xueru; Li, Hongwei; Yang, Yidong; Qian, Dong; Fu, Xiaolong (Frontiers in Oncology, 2021)
Background We aimed to analyze the first progression sites of first-line tyrosin kinase inhibitor (TKI) treatment for EGFR-mutant lung adenocarcinoma patients with systemic metastasis to recognize the potential candidates who might benefit from radiotherapy and establish a radiomic-based model to predict the first progression sites. Materials and Methods We retrospectively collected the clinical information and pre-treatment chest CT images of patients in Shanghai Chest Hospital from 2013 to 2017. All patients were diagnosed with stage IV EGFR-mutant lung adenocarcinoma and received TKI as first-line treatment. The first progression sites and survival were analyzed. The pre-treatment chest non-contrast CT images were utilized to establish a radiomic-based model to predict the first progression sites. Results We totally collected 233 patients with systemic metastasis, among whom, there were 84 (36.1%) and 149 (63.9 %) patients developing first progression in original lesions (OP) and new lesions (NP) respectively. The PFS and OS of patients with OP were longer than those with NP (PFS 11 months vs. 8 months p=0.03, OS 50 months vs. 35 months p=0.046). For 67.9% of the patients with OF, disease progressed within five sites (oligoprogression). The radiomic-based model could predict the progression sites with an AUC value of 0.736, specificity of 0.60 and sensitivity of 0.750 in the independent validation set. Conclusion Among patients with systemic metastasis, there were 36.1% patients developing OP at first progression who had a better prognosis than those developing NP. Patients with OP may be the potential candidates who might benefit from radiotherapy. Radiomics is a useful method to distinguish patients developing OP and could provide some indications for radiotherapy.